ERP sebagai Pilar Sistem Pengendalian Manajemen: Menganalisis Dampak pada Efisiensi dan Akuntabilitas Perusahaan - Febi Theresia Immanuel; I. B. Ketut Bayangkara (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Enterprise Resource Planning (ERP) systems have become the operational backbone of many modern companies, not only as a data integration tool but also as a crucial pillar in management control systems (MCS). This study aims to comprehensively analyze the impact of ERP implementation on operational efficiency and corporate accountability. Using a qualitative approach through literature study and case review, this study explores how ERP facilitates real-time and integrated information flow, which in turn improves managerial decision-making capabilities, resource optimization, and increased transparency and accountability at various levels of the organization. The results show that ERP contributes significantly to increased efficiency through process standardization and reduced redundancy, and strengthens accountability by providing clear audit trails and reliable data. However, the success of the implementation is highly dependent on factors such as top management support, adequate employee training, and alignment with business strategy.